PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN MAKAN DENGAN SENDOK PADA ANAK AUTIS DI SLB AUTIS - Alifia, Cikita (Jurnal Pendidikan Khusus, 2017)
Abstrack : Contextual approach is a concept of learning by linking the subject matter to everyday life in the context of personal, social and cultural life. Self care is a program of programmed and planned training activities and guidance on the personal care of children with special needs. This study aims to obtain increased ability to eat with a spoon through a contextual approach in children with autism in SLB Autis Mutiara Hati Sidoarjo. Approach in this research is quantitative, data collecting technique in this research is observation. Observation techniques are used as an assessment sheet on pretest and posttest activities. The results of this study show that Zh (2.20)> Zt (1,96) shows that there is influence of contextual approach to eating with spoon on autistic children in SLB Autis Mutiara Hati Sidoarjo.   Keyword : Contextual approach, eating with a spoon